INNOVATION-ORIENTED ENTREPRENEURSHIP AS A FACTOR OF EFFECTIVE DEVELOPMENT OF AGRICULTURE IN THE REGION - Elena V. Chemodanova (Вестник Северо-Кавказского федерального университета, 2022)
This article shows the relevance and importance of innovative entrepreneurship in the modern economy: world experience and in Russia. Assess the current status and use of the economic potential of the Stavropol region, identifies the main problems of innovation activity in the region, namely the current funding mechanism, namely the low proportion of State participation in the innovation processes. The necessity of development and innovation processes in the agro-industrial complex of the region and propose an alternative solution to the problem.